Digitization of the Arda cascade for the hydroelectric production - part I - Petrov, Hristiyan; Petrov, Georgi (Yearbook Telecommunications, 2021)
The digitalization of the energy sector is an important factor for the development of the economy and industry, the article discusses a hypothetical model for a transitional phase in the digitalization of one of the most important hydroelectric systems in Bulgaria, the Arda cascade. The introduction of digital systems achieves a number of advantages: creates prospects for intelligent support, improves work efficiency, creates conditions for creating a "digital" twin, achieves a drastic increase in security of the site and the whole system, improves communication during implementation of infrastructure reconstructions, etc.